SPECIAL MEASURES OF ANTI-HELMINTOSES COMPLEX IN CASE OF GOOSE ENDO- PARASITOSES (ANSER ANSER DOMESTICUS & ANSER CYGNOIDES DOMESTICUS, LINNAEUS, 1758) - Yuskiv, I. D.; Melnychuk, V. V. (Scientific Progress & Innovations, 2020)
Data as to the most widely spread causal agents of goose helminthic diseases (Anser anser domesticus & Anser cygnoides domesticus Linnaeus, 1758), which are of interest for veterinary doctors, have been pre- sented in the article. Chemical-therapeutic preparations, available on the pharmaceutical market of Ukraine and used for treatment and prevention in goose breeding, have been listed. The main causal agents of goose endo-parasitic diseases have been considered taking into account the modern parasites’ system position. The peculiarities of their biology and epizootology on the territory of Ukraine in accordance with the data of well-known scholars researching veterinary parasitology have been briefly presented. The information has been generalized concerning the peculiarities of using anti-helminthic preparations for the treatment of goose trematodoses, cestodoses, nematodoses, and acanthocephaloses. The information as to the most wide- ly spread preparations and chemical compounds, which are active substances of these preparations, has been given in the paper (their chemical names in different countries of the world, and also synonyms, struc- tural formulas, the main physical properties). The information has been given concerning the dosage and peculiarities of applying chemical-therapeutical preparations for the treatment of goose endo-parasitic dis- eases in accordance with the data in the modern scientific literature and corresponding recommendations for conducting post-dehelminthization period in case of various helminthoses. The groups of anti-helminthic means were considered: benzimidazols, imidothiazols, macro-cyclic lactones, salicylanilides, and also com- bined agents having several active substances in their composition. The aim of the given paper has been to show the modern state concerning goose endo-parasitic diseases both on the territory of Ukraine and in the whole world, single out the available anti-helminthic preparations, generalize the information concerning their using, and also point out the important moments of post-dehelminthization period. The conducted anal- ysis of literary sources will enable to expand the existing data concerning the pathogens of parasitic etiolo- gy, which cause considerable economic losses in goose breeding sector. The data presented in the article will help specialists of veterinary medicine choose the necessary effective chemical-therapeutical prepara- tion for the treatment of certain helminthosis or its association development. In its turn, the given infor- mation will help ensure veterinary well-being on goose farms of Ukraine, which will enable to create the flocks of healthy and highly productive poultry.